Uma querela de espíritos: para uma crítica brasileira do suposto desencantamento do mundo moderno - Carvalho, José Jorge de (2022)
In this essay I try to offer a general model of interpretation of the Brazilian religious diversity focusing my analysis in the constant enchantment produced by periferic or marginal religions, such as the ones known as “spiritualist" and those of African origin. This new perspective allows me to challenge two theoretical tendencies which are dominant among our social scientists: to read the reality of Brazilian religiosity always from the point of view of the transformations that take place inside the Christian movements; and to use acritically the hypothesis of secularization, developed to uderstand the decline of the religious sphere in Europe and the United States, in order to interpret our national religious space. By using the metaphor of the “war of spirits" I argue that what we observe in Brazil today is a struggle, not to turn it into a more secular society, but the other way round: an attempt to expand the religious dimension of the public space